Recombinant Flagellin A Proteins from Borrelia burgdorferi Sensu Stricto, B. afzelii, and B. garinii in Serodiagnosis of Lyme Borreliosis - Panelius, Jaana (American Society for Microbiology, 2001)
Genes for flagellin A (FlaA) proteins from European borrelial strains of Borrelia burgdorferi sensu stricto, B. afzelii, and B. garinii were cloned and sequenced. An identity of 92 to 93% was observed in the flaA sequences of the different species. Polyhistidine-tagged recombinant FlaA (rFlaA) proteins were produced in Escherichia coli and used as antigens in Western blotting (WB) and enzyme-linked immunosorbent assay (ELISA). In immunoglobulin G (IgG) WB, 71% (10 of 14) of the sera from neuroborreliosis and 86% (12 of 14) of those from Lyme arthritis patients reacted with one to three rFlaAs. In IgG ELISA, 74% (14 of 19) and 79% (15 of 19) of patients with neuroborreliosis and arthritis, respectively, were positive. The immunoreactivity in local European patient sera was stronger against rFlaA from B. garinii and B. afzelii than against rFlaA from B. burgdorferi sensu stricto. Neither IgG nor IgM ELISA was sensitive in the serodiagnosis of erythema migrans. Serum samples from patients with syphilis and systemic lupus erythematosus showed mild cross-reactivity in IgG tests. Sera from Yersinia enterocolitica or beta-hemolytic Streptococcus infections showed only occasional responses. With IgM ELISA, 58% (11 of 19) and 37% (7 of 19) of patients with neuroborreliosis and arthritis, respectively, were positive. Cross-reactive antibodies to FlaA, especially in serum samples from patients with rheumatoid factor positivity and Epstein-Barr virus infection, reduced the specificity of IgM serodiagnosis. Therefore, rFlaA seems to have a limited role for IgM serodiagnosis, yet rFlaA might be useful in the IgG serodiagnosis of disseminated Lyme borreliosis.